Ocular changes associated with Giardia lambliainfection in children. Issue 1 (1st January 1998) - Corsi, A; Nucci, C; Knafelz, D; Bulgarini, D; Di Iorio, L; Polito, A; De Risi, F; Morini, F Ardenti; Paone, F M
Abstract : BACKGROUND: The protozoan disease giardiasis can cause ocular complications, including "salt and pepper" retinal changes. METHODS: Ophthalmic examinations were performed in 141 children (mean age 4.7 (SD 2.0) years) with active or past giardiasis diagnosed on the basis of microscopic examination of stool specimens or duodenal secretions—53 were newly diagnosed and untreated (group A), 50 had active infections in spite of metronidazole therapy (group B), and 38 had been successfully treated, with negative stool specimens for 1–3 years (group C). 300 children with no evidence of giardiasis were used as controls. RESULTS: Salt and pepper retinal changes (with normal electroretinographic findings) were diagnosed in 28 (19.9%) of the patients with giardiasis (11 from group A, 10 from group B, and seven from group C), including five pairs of siblings. In all subgroups, the children with retinal changes were consistently younger than those with normal retinas. In eight cases, the lesions could be visualised only with direct ophthalmoscopy. CONCLUSION: Our findings indicate that asymptomatic, non-progressive retinal lesions are particularly common in younger children with giardiasis. This risk does not seem to be related to the severity of the infection, its duration, or the use of metronidazole but may reflect a genetic predisposition.